Technological maturity of hybrid vine (Vitis) fruits under Estonian climate conditions - Mariana Maante-Kuljus; Reelika Rätsep; Leila Mainla; Ulvi Moor; Marge Starast; Priit Põldma; Kadri Karp (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2019)
Vine growing is gaining popularity around the Baltic Sea and the production of commercial wine is also increasing in Estonia. The aims of the experiment were: evaluate the suitability of different grape cultivars for growing in Estonian climate according to Heliothermal Index; determine the wine grapes technological maturity of ‘Hasansky Sladky’, ‘Zilga’ and ‘Rondo’ over 10 years; determine the effect of vineyard locations with different cultivation systems (polyethylene tunnel and field) on wine grapes technological maturity and acids composition of ‘Rondo’. In the field conditions, the soluble solids content ranged from 12.0 to 21.2 °Brix. Titratable acids content ranged from 6.5 to 22.7 g L−1 and the pH was between 2.8 and 3.9. Growing ‘Rondo’ in tunnel increased soluble solids and decreased total acids content. Tartaric acid content ranged from 3.6 to 5.5 g L−1 in field and from 3.7 to 4.3 g L−1 in the tunnel. In the field, malic acid in grapes was significantly higher (5.2–7.8 g L−1) when compared to grapes grown under tunnel conditions (1.9–3.6 g L−1). Estonia is classified as a region with very cool climate for vine cultivation. The latter indicates to the existence of the heliothermal potential for growing early cultivars.